Use of Reference Management Software by Faculty and Research Scholars at IIT Gandhinagar: An Exploratory Study - Chaudhari, Panna; Kumbar, T. S.; Gadhvi, Geeta (Journal of Data Science, Informetrics, and Citation Studies)
This study investigates the adoption and utilization patterns of Reference Management Software (RMS) among research scholars and faculty at the Indian Institute of Technology (IIT) Gandhinagar. Through comprehensive surveys conducted across various departments, the research identifies key trends in software preference, the extent of usage, and the challenges encountered in managing bibliographic references. The findings reveal that while RMS tools like Mendeley and Zotero are widely recognized, actual usage varies significantly between faculty and research scholars. The study also examines the role of library services in supporting RMS adoption, highlighting the need for enhanced institutional support to optimize research workflows. The insights gathered provide valuable recommendations for improving the effectiveness of research support services in academic institutions.
Keywords: Reference Management Software; Research Scholars; Faculty; IIT Gandhinagar; Academic Libraries; Research Support Services; Mendeley; Zotero; Citation Management Software; Digital Tools Adoption.